Analysis of CPO Exports Using the Gravity Model Approach: Indonesian CPO Exports with Competitor Malaysia in the Main Markets of China and India - Nissa Nur Awaliyah; Haryo Kuncoro; Karuniana Dianta Arfiando Sebayang (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to determine the Revealed Comparative Advantage analysis and the gravity model approach of Indonesian CPO exports with competitor Malaysia in the main markets of China and India. This study employs the RCA competitiveness method and determinant analysis using panel data regression. The analysis tool used is E-Views 12. This study utilizes secondary data from the two main crude palm oil-producing countries, Indonesia and Malaysia, in the largest CPO export markets of China and India. The data sources for this study include UN Comtrade, Trading Economics, Time and Date, World Development Indicators, the World Bank, previous studies, research journals, books, and other literature. The results of this study indicate that both Indonesia and Malaysia have an RCA value greater than 1. However, Indonesia is more advantageous than Malaysia. Economic distance has a positive and significant impact on the volume of CPO exports from Indonesia and Malaysia. International CPO prices have a negative and significant impact on Indonesia's CPO export volume. International CPO prices have a negative but insignificant impact on Malaysia's CPO export volume. Exchange rates have a negative and significant impact on Indonesia's and Malaysia's CPO export volumes. The real GDP of export destination countries has a positive but insignificant impact on Indonesia's and Malaysia's CPO export volumes.